Untersuchungen zum Vorkommen ausgewählter Zooanthroponose-Erreger bei Rentieren unter dem Aspekt der aktuellen Situation der finnischen Rentierwirtschaft - Kemper, Nicole (Tierärztliche Hochschule, 2004)
The information about pathogens excreted by semidomesticated reindeer (Rangifer tarandus tarandus) that might represent a health risk to humans and animals is insufficient. Infections may be accomplished through direct contact, consumption of contaminated reindeer meat or through contamination of the environment due to faecal shedding. The objectives of this study, that was performed as part of the EU-project RENMAN (www.urova.fi/home/renman/), were to figure out the occurrence and prevalence of important zoonotic pathogens in reindeer. Faecal material from 2 243 clinically healthy reindeer from northern regions of Finland and Norway was sampled, considering parameters such as degree of intensification of husbandry, location and season. Furthermore 431 soil samples were analysed to get an impression of the environmental contamination. Samples were examined for important zoonotic bacteria (Campylobacter spp, Enterococcus spp, Escherichia coli, Salmonella spp and Yersinia spp) and parasites (Cryptosporidium) following standard procedures. Escherichia coli were isolated in 2 123 (94.7%), Enterococcus spp in 2 084 (92.9%), Yersinia spp in 108 (4.8%) and Campylobacter sp, identified as C. hyointestinalis, in one sample only (0.04%). Neither Salmonella spp nor Cryptosporidium-oocysts were detected. Only few of the isolated E. coli-strains possess genes encoding stx1 (0.14%), stx2 (0%), eae (0.61%) and hlyEHEC(1.08%), detected by PCR, that have the ability to cause health problems in humans and animals. The isolated Yersinia spp were further analysed for virulence factors, but examinations revealed no pathogenic strains. In the soil samples, the few isolated bacteria could not be identified as reindeer-originated. However, the samples of the more intensively grazed Finnish side showed more bacteria than samples from the Norwegian side, where reindeer graze only at certain times of the year. This study clearly shows that E. coli and Enterococcus spp belong to the normal intestinal flora of healthy reindeer. Even though ...